High LDL levels are associated with increased lipoprotein-associated phospholipase A2 activity on nitric oxide synthesis and reactive oxygen species formation in human endothelial cells - Searle, Andrea (2011)
Objective: To evaluate in vitro the effects of serum and LDL fractions isolated from hypercholesterolemic patients on nitric oxide (NO) synthesis and reactive oxygen species (ROS) production by human umbilical vein endothelial cells (HUVECs). Design and methods: Serum and LDL isolated from subjects with high (n=18) and normal (n=21) LDLcholesterol levels were analyzed on NO synthesis and ROS production in vitro models of HUVECs. LDL was furthers characterized in their chemical composition and activities of lipoprotein-associated phospholipase A2 (Lp-PLA2), cholesteryl ester transfer protein (CETP) and paraoxonase. Results: NO bioavailability was significantly lower and ROS production higher in HUVECs incubated with serum samples from patients with high LDL-cholesterol levels in comparison to control subjects. Moreover, hypercholesterolemic patients presented higher CETP and Lp-PLA2 activities than control subjects. LDL fractions isolated from patients and controls were not different in their chemical composition, Lp-PLA2 activity, and their capacity to reduce NO synthesis and increase ROS production. Conclusion: Alterations of serum from hypercholesterolemic patients could be due to the increment in LDL concentration, main Lp-PLA2 carrier, and not to LDL composition or intrinsic Lp-PLA2 activity.